2023
DOI: 10.3390/ph16121696
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Endometriosis: Exploring the Relationship and Therapeutic Implications

Anjeza Xholli,
Francesca Cremonini,
Isabella Perugi
et al.

Abstract: Endometriosis is a common inflammatory disease affecting women of reproductive age, characterized by the growth of endometrial tissue beyond the uterus. In addition to gynecological manifestations, many endometriosis patients experience gastrointestinal symptoms, indicating a potential association between gut health and the disease. Recent studies have revealed alterations in the gut microbiota of individuals with endometriosis, including reduced diversity, microbial composition imbalances, and pathogenic bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The study suggests a potential association between impaired intestinal permeability and endometriosis, emphasizing the need for further research to understand its role in the pathogenesis and potential diagnostic implications for endometriosis (Mohling et al, 2023). Xholli et al explored the role of zonulin, a protein responsible for regulating intestinal permeability, which could help elucidate the presence of gastrointestinal symptoms in endometriosis patients (Xholli et al, 2023).…”
Section: Gut Microbiome In Emsmentioning
confidence: 99%
“…The study suggests a potential association between impaired intestinal permeability and endometriosis, emphasizing the need for further research to understand its role in the pathogenesis and potential diagnostic implications for endometriosis (Mohling et al, 2023). Xholli et al explored the role of zonulin, a protein responsible for regulating intestinal permeability, which could help elucidate the presence of gastrointestinal symptoms in endometriosis patients (Xholli et al, 2023).…”
Section: Gut Microbiome In Emsmentioning
confidence: 99%
“…To date, correction of the gut microbiota with antibiotics, probiotics, or fecal bacterial transplantation is a hopeful method for improving the clinical management of endometriosis. [49,50,51] Authors Contribution:…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Recent studies have demonstrated a close association between gut microbiota and the onset and development of various diseases, including diabetes ( Yang et al, 2021 ), irritable bowel syndrome (IBS) ( Salmeri et al, 2023b ), colon cancer ( Novello et al, 2019 ), and polycystic ovary syndrome ( Liang et al, 2021 ). Up to 90% of patients with endometriosis report gastrointestinal symptoms, such as bloating, nausea, constipation, diarrhea, and vomiting ( Xholli et al, 2023 ), in addition to gynecological symptoms. This situation suggests a potential link between gut health and endometriosis.…”
Section: Introductionmentioning
confidence: 99%